Infantile acropustulosis. A late diagnosis. - Santos, G.; João, A.; Paiva Lopes, M.J. (European Journal of Pediatric Dermatology, 2012)
Infantile acropustulosis is a recurrent, pruritic, vesicopustular eruption that is frequently misdiagnosed as recurrent scabies. We present an 8-month-old black boy with very pruritic papules on his wrists and ankles, treated repeatedly with antiscabietic agents. A punch biopsy was done and revealed findings consistent with acropustulosis. The cutaneous lesions improved with topical corticosteroids and resolved after 2 years of this intermittent treatment.